(untitled) (Proceedings of Faculty of Civil Engineering, 2019)
This paper presents a description of the water mass oscillation on the accumulation system – inlet pipe - water chamber, as well as a description of the occurrence of a water hammer due to the sudden closure of the shutter on a given system. For the purpose of obtaining the relevant hydrodynamic analysis of the water mass oscillation in the cylindrical water chamber, experimental measurements were carried out on the physical model GUNT HM156, which is an integral part of the measuring instrument of the hydro technical laboratory of the Faculty of Civil Engineering of the University of Rijeka. The hydrodynamic analysis was carried out based on more experimental trials, in which the input water values were the changeable upper water level in the accumulation and the different water influx (flow) in the cylindrical water chamber regulated by the ball valve. The hydrodynamic analysis is based on two separate parts. In the first part, only the water mass oscillation in the water chamber at the sudden closing of the solenoid valve has been considered, while the second part of the analysis is related to the occurrence of a water hammer, and the defining of the velocity propagation of pressure disorders in the water. For the purposes of the research on the physical model, sophisticated measurement technique as well as the oscilloscope were used.